PENDIDIKAN NILAI-NILAI ISLAM PADA REMAJA PERKOTAAN (Studi tentang Aktivitas Dakwah Bikers Subuhan Manado) - Mardan Umar; Mona Fatnia Mamonto; Ismail K Usman (Journal Civics and Social Studies, 2020)
This study aims to examine efforts to educate Islamic values in urban youth, especially in Bikers Subuhan Manado. The research problem raised is how the efforts to educate Islamic values in Bikers Subuhan Manado, the programs implemented and what factors influence the education of Islamic values in urban youth. This research uses a qualitative approach. Data collection techniques include observation, interviews, and documentation. The results of this study indicate that efforts to educate Islamic values in urban youth, especially in the Bikers Subuhan Manado, are carried out with dawn congregation activities from mosque to mosque, Islamic religious studies, and mosque cleaning activities. The implementation of the Bikers Subuhan Manado program is aimed at increasing adolescent insights about Islamic values, improving worship, without leaving hobbies such as gathering and riding motorbikes. Factors supporting the educational activities of Islamic values in urban youth are the characteristic concepts and approaches of adolescent coaching, the existence of social media as a means of socializing programs and platforms for the existence of adolescents and support from the community. While the inhibiting factors are psychological factors of adolescents and lack of activity funding support.